Pemberdayaan Masyarakat Melalui Digital Marketing Sebagai Media Promosi Di Umkm Kecamatan Coblong - Budiman Budiman; Catherin Rumambo Mogot Pandin (LPPM Universitas Informatika dan Bisnis Indonesia, 2022)
One of the economic strengths that supports the Indonesian economy and regional economic strength is the existence of micro, small and medium enterprises. In addition to the support of large industries, the state tax sector received considerable support from small industry groups, which were able to maintain and increase the contribution of regional economic growth. To overcome these problems, training and assistance will be provided. The aim is to provide an understanding of the importance of digital marketing for MSMEs in increasing income. The output target of this activity is to provide knowledge about the importance of digital marketing for MSME actors, add soft skills regarding insights on how to manage information technology-based products and marketing, and foster a technopreneur spirit among MSME players.